Henrique joão wilkens: a pioneer poet in the amazonia (2013)
This literary biographical article deals with the life and work of Henrique João Wilkens, author of the first epic poem written in the Amazon, Muhuraida ou, O triunfo da fé (Muhuraida or The Triumph of the Faith), of 1785. This courageous adventurer was one of the main Amazonian characters of the XVIII Century; however, little is known about this man. Bases on bibliographic research, this article addresses the life of Wilkens, his nationality, his role in the Portuguese Army, the places where he lent his services to the Portuguese Crown and to the State of Grand Para, his family and his work, with the aim to make him better known in the academic context.